Fine-scale movement of humpback whales (Megaptera novaeangliae) in Icelandic coastal waters - Sydni Anne Long 1997- (2023)
Verkefnið er lokað til 30.09.2024 North Atlantic humpback whales (Megaptera novaeangliae) typically participate in yearly, seasonal migrations between low latitudinal calving grounds in winter and high latitude feeding grounds in summer. While these long-distance migrations are well understood, the movement of whales within the feeding area is not. This project investigates movements of 435 identified humpback whale individuals in Icelandic coastal waters. Their sighting histories spans over a 10-year period (2011 and 2020) and are centralised in the ÍSland Megaptera novaeangliae (ISMN) catalogue curated by the Marine and Freshwater Research Institute (MFRI). Arrival and movement direction of each humpback individual was based on date and location of the first and the last sighting every year. This analysis revealed information on site fidelity and arrival patterns of individuals. Statistical analysis did not indicate a significant difference in the direction the whales moved after arrival; however, the majority travelled northward. To determine possible drivers to the observed movement, analyses using Pearson Correlation tests were conducted on whale sightings per unit effort (SPUE) from Faxaflói Bay (south) and Eyjafjörður and Skjálfandi Bay (Northeast) versus proportional forage fish prey of herring (Clupea harengus) and capelin (Mallotus villosus) from the International Ecosystem Summer Survey of the Nordic Seas from the MFRI. This analysis showed no statistically significant results for correlation between proportional forage fish sample and SPUE. Regardless, this research provides new insights into the movement of humpback whales in Iceland, including possible overlap between humpback whale movements and humans (fishers, industry, tourism), which can inform fisheries and marine spatial legislation, plus whale watching tourism in high-use habitat regions. It also provides a starting point for investigation of predator-prey relationships for further management of Icelandic fisheries and demonstrates the ...